The Influence of Analysts, Institutional Investors, and Insiders on the Incorporation of Market, Industry, and Firm-Specific Information into Stock Prices - Piotroski, Joseph D.; Roulstone, Darren T. (The Accounting Review, 2004)
We investigate the extent to which the trading and trade-generating activities of three informed market participants—financial analysts, institutional investors, and insiders—influence the relative amount of firm-specific, industry-level, and market-level information impounded into stock prices, as measured by stock return synchronicity. We find that stock return synchronicity is positively associated with analyst forecasting activities, consistent with analysts increasing the amount of industry-level information in prices through intra-industry information transfers. In contrast, stock return synchronicity is inversely related to insider trades, consistent with these transactions conveying firm-specific information. Supplemental tests show that insider and institutional trading accelerate the incorporation of the firm-specific component of future earnings news into prices alone, while analyst forecasting activity accelerates both the industry and firm-specific component of future earnings news. Our results suggest that all three parties influence the firm's information environment, but the type of price-relevant information conveyed by their activities depends on each party's relative information advantage.